2019
DOI: 10.1126/scitranslmed.aau7746
|View full text |Cite
|
Sign up to set email alerts
|

GPRC5D is a target for the immunotherapy of multiple myeloma with rationally designed CAR T cells

Abstract: Early clinical results of chimeric antigen receptor (CAR) T cell therapy targeting B cell maturation antigen (BCMA) for multiple myeloma (MM) appear promising, but relapses associated with residual low-to-negative BCMA-expressing MM cells have been reported, necessitating identification of additional targets. The orphan G protein–coupled receptor, class C group 5 member D (GPRC5D), normally expressed only in the hair follicle, was previously identified as expressed by mRNA in marrow aspirates from patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
230
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(232 citation statements)
references
References 34 publications
1
230
0
1
Order By: Relevance
“…CAR T cells that are generated by fusing APRIL, a ligand for BCMA and TACI, with T cell-activating molecules are also shown to be effective in pre-clinical experiments [36]. Smith et al in Memorial Sloan Kettering Center recently reported GPRC5 as a promising target for CAR T cells against MM [37]. Not reported yet - [38] We also developed a new CAR T cell for MM.…”
Section: Development Of Car T-cells Targeting Antigens Other Than Bcmmentioning
confidence: 99%
“…CAR T cells that are generated by fusing APRIL, a ligand for BCMA and TACI, with T cell-activating molecules are also shown to be effective in pre-clinical experiments [36]. Smith et al in Memorial Sloan Kettering Center recently reported GPRC5 as a promising target for CAR T cells against MM [37]. Not reported yet - [38] We also developed a new CAR T cell for MM.…”
Section: Development Of Car T-cells Targeting Antigens Other Than Bcmmentioning
confidence: 99%
“…In addition to bispecific antibodies and ADCs in early clinical development, there are now at least two CAR-T therapies in the research pipeline at the preclinical stage. These target EMR1, an aGPCR, for the treatment of eosinophilic leukemia [72] and GPRC5D, an orphan GPCR, for the treatment of multiple myeloma [73]. Another important area of interest in the field of antibody engineering is the use of BBB receptor-mediated transcytosis delivery (e.g., via the transferrin receptor) which could equally be applied to GPCR targeting using antibody-based modalities.…”
Section: Next-generation Modalitiesmentioning
confidence: 99%
“…Recently, 2 groups independently reported that the orphan G protein-coupled receptor, class C group 5 member D (GPRC5D), is specifically expressed in MM cells [18,19]. A group identified GPRC5D-specific scFvs and used them to generate CAR T cells [18]. One of the GPRC5D-targeted CAR T cells eradicated MM and enabled long-term survival in mouse models.…”
Section: Grpc5d As a Novel Target For Car T Cell Therapy Against MMmentioning
confidence: 99%